2006
DOI: 10.1038/sj.bjp.0706847
|View full text |Cite
|
Sign up to set email alerts
|

Protection from experimental colitis by theaflavin‐3,3′‐digallate correlates with inhibition of IKK and NF‐κB activation

Abstract: Background and purpose: Inflammatory bowel disease (IBD) is associated with activation of nuclear factor kappa B (NF-kB) involved in regulating the expression of inducible nitric oxide synthase (iNOS) and proinflammatory cytokine genes. As theaflavin-3,3 0 -digallate (TFDG), the most potent anti-oxidant polyphenol of black tea, down-regulates NF-kB activation, we investigated if TFDG is beneficial in colonic inflammation by suppressing iNOS and proinflammatory cytokines. Experimental approach: The in vivo effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 58 publications
(59 reference statements)
6
74
0
Order By: Relevance
“…The results suggest that the action of polyphenol-containing GFW in blocking the migration and adhesion of monocytes to the colon epithelial cells are mediated through regulation of NF-κB activity. These results are consistent with previous findings of the inhibitory effects of polyphenols on NF-κB activity associated with inflammation (Kundu and Surh, 2004;Ukil et al, 2006).…”
Section: Discussionsupporting
confidence: 83%
“…The results suggest that the action of polyphenol-containing GFW in blocking the migration and adhesion of monocytes to the colon epithelial cells are mediated through regulation of NF-κB activity. These results are consistent with previous findings of the inhibitory effects of polyphenols on NF-κB activity associated with inflammation (Kundu and Surh, 2004;Ukil et al, 2006).…”
Section: Discussionsupporting
confidence: 83%
“…[41][42][43][44][45][46] Very recently, it has been shown that glutamine given by intragastric gavage reduces immunohistochemical expression of NF-B in the colon of animals treated with TNBS, 21 and activation of NF-B in rats with acetic acid-induced colitis. 1 Our data further demonstrate that inhibition of the nuclear translocation of p50 and p65 subunits contribute to the protective effect of glutamine in rats with experimental colitis.…”
Section: Discussionmentioning
confidence: 98%
“…The theaflavins consist of theaflavin, theaflavin-3-gallate, theaflavin-3 0 -gallate and theaflavin-3,3 0 -gallate. Theaflavins have been suggested to reduce oxidative stress and inflammation in studies in vitro and in vivo [8][9][10][11][12][13][14]. However, although black tea is the most widely consumed beverage, the precise mechanisms by which black tea polyphenols exert these protective effects have not yet been as thoroughly elucidated as with green tea.…”
Section: Introductionmentioning
confidence: 99%